2019
DOI: 10.1002/hed.25985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human papillomavirus status on survival and recurrence in a geographic region with a low prevalence of HPV‐related cancer: A retrospective cohort study

Abstract: Background: Human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma (OPSCC) is associated with better tumor-response rates and survival outcomes. However, in some geographic regions, the impact of HPV infection on prognosis remains unclear. The aim of this study was to describe the patterns of recurrence and survival among patients treated for OPSCC in a geographic region with a reported low prevalence of HPV-related OPSCC. Methods: We retrospectively evaluated 215 patients diagnosed with Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
5
18
0
4
Order By: Relevance
“…There was a higher prevalence of patients who never drank in the p16 + group than in the p16 − group (16% vs. 2.7%, P = 0.015). De Cicco et al [ 28 ] and López et al [ 26 ] found similar results. In comparison, Bahl et al [ 29 ] did not find evidence of a correlation between alcohol consumption and HPV positivity (P = 0.18).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…There was a higher prevalence of patients who never drank in the p16 + group than in the p16 − group (16% vs. 2.7%, P = 0.015). De Cicco et al [ 28 ] and López et al [ 26 ] found similar results. In comparison, Bahl et al [ 29 ] did not find evidence of a correlation between alcohol consumption and HPV positivity (P = 0.18).…”
Section: Discussionsupporting
confidence: 55%
“…However, specifically in the p16 + group, there was a proportionally larger number of patients with early clinical stages (I and II) compared to the p16 − group (52.6% vs. 13.1%, P < 0.001). De Cicco et al [ 28 ] and Du et al [ 31 ] reported similar results.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In Brazil, studies found a low prevalence of HPV in oropharynx tumors ranging from 4.4% to 8.8% [18][19][20]. Conversely, patients from a private hospital had an HPV positivity rate of 59.1% [21], which demonstrates the HPV heterogeneity in the country. Due to these discrepancies in the prevalence of HPV, it is crucial to monitor these subsites to clarify whether this dramatic shift in incidence trends observed worldwide also affects this population.…”
Section: Introductionmentioning
confidence: 95%